Mental health effects of exposure to environmental noise at home: A systematic review of potential mediating pathways - Kaya Grocott; Adelle Mansour; Eleanor Shiels; Rebecca Bentley; Kate Mason (Noise and Health)
Objective: Research has established a mental health impact of exposure to environmental noise, but specific mechanisms driving this association are poorly understood. Several plausible mediating factors have been proposed, including noise annoyance and sleep disturbance. We undertook a systematic review of the literature to synthesize the existing evidence on possible mediating pathways between exposure to environmental noise and poor mental health in adults. Methods: We systematically searched Medline, PsycINFO, Embase, and Web of Science databases to identify relevant studies published up to May 2023. Studies of the mental health impact in adults of environmental noise at home that examined at least one mediator were included. Included studies were assessed for risk of bias. Findings from included studies were synthesized narratively. Study heterogeneity and high risk of bias precluded meta-analysis. Results: Of the 892 studies retrieved, 14 met the inclusion criteria. These spanned 13 unique mediators. Some studies examined multiple mediators. The most commonly examined mediators were noise annoyance (nine studies), sleep disturbance (four studies), and physical activity (two studies). Taken together, these studies provide support for noise annoyance and sleep playing a role in the mediation of the noise-mental health association, while evidence was limited or absent for other mediators. The small number of studies and high risk of bias leads to low certainty of evidence. Conclusions: Noise annoyance and sleep disturbance are likely mediators of the relationship between exposure to environmental noise at home and poor mental health. However, higher quality and longitudinal researches are needed to clarify these and other potential mediating pathways.